Introduction: Key issues and policies for extending working life - Ogg, Jim; Rašticová, Martina (Springer Switzerland, 2020)
Extended working life policies have been widely promoted in Europe and in wider international settings. However, to date, these policies have not, for the most part, taken sufficient account of the gender and health dimensions of working longer. This chapter outlines the empirical and policy landscapes that are present in Europe and several other countries. It examines the different meanings of 'extended working life' and the indicators used to justify raising the age of eligibility for a pension. Gender and health inequalities related to extended working life, such as gender pay and pension gaps and differential life expectancy rates are presented. The influence of the labour market on the employability of older workers is examined in the context of economic downturns and digitalisation. The chapter concludes that policy initiatives which meet the diverse needs of older workers and which address gender and health inequalities related to extended working should be a priority for governments and employers in the years ahead.
Keywords: Eligibility for pension; Extended working life policies; Work inequalities; Gender; Health